The Three Genres and the Interpretation of Lyric - Rogers, William Elford (Book collections on Project MUSE., 1983)
William Elford Rogers proposes a genre-theory that will clarify what we mean when we speak of literary works as dramatic, epic, or lyric. Focusing on lyric poetry, this book maintains that the broad genre-concepts need not be discarded but can be preserved by a new interpretive model that gives us conceptual knowledge not about works but about interpretation. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.